Peran Media Sosial Instagram Dalam Pembentukan Konsep Diri Siswa SMP Negeri 3 Cibaliung - Kartini, Uyun; Haryono (CV. Ulil Albab Corp, 2025)
The development of digital technology and the widespread use of social media have had an impact on various aspects of life, one of which is the formation of adolescent self-concept. Social media functions as a platform for individuals, especially students, to express themselves, share experiences, and build self-identity. This study aims to examine the role of social media in the formation of students' self-concept, with a focus on how they view themselves and how they want to be perceived by others. This study uses a descriptive qualitative approach with interview, observation, and documentation methods to dig deeper into information about students' experiences and perceptions of social media. The results of the study indicate that social media has a very large role in the formation of students' self-concept. The use of social media allows students to explore their self-identity through images, statuses, and interactions with online friends, which contributes to efforts to find identity and social recognition based on actions, thoughts, self, and society.